2016
DOI: 10.1371/journal.pone.0159515
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Radiotherapy with 3 x 8 Gy Induces Systemic Anti-Tumour Responses and Abscopal Tumour Inhibition without Modulating the Humoral Anti-Tumour Response

Abstract: Accumulating evidence indicates that fractionated radiotherapy (RT) can result in distant non-irradiated (abscopal) tumour regression. Although preclinical studies indicate the importance of T cells in this infrequent phenomenon, these studies do not preclude that other immune mechanisms exhibit an addition role in the abscopal effect. We therefore addressed the question whether in addition to T cell mediated responses also humoral anti-tumour responses are modulated after fractionated RT and whether systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
1
42
0
1
Order By: Relevance
“…From these studies, it is also evident that different immunotherapeutic agents can boost abscopal responses by targeting different aspects of the immune-mediated response 9,17,27 . For example, FLT3L can be used to recruit and stimulate APCs 17,18,32 , anti-CD40 can be employed to increase activation of APCs 33 , and anti-CTLA4 or antibodies against programmed cell death protein 1 (PD1) can act as immune checkpoint inhibitors, increasing the T cell activity directed against tumour cells 23,26,34 .…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…From these studies, it is also evident that different immunotherapeutic agents can boost abscopal responses by targeting different aspects of the immune-mediated response 9,17,27 . For example, FLT3L can be used to recruit and stimulate APCs 17,18,32 , anti-CD40 can be employed to increase activation of APCs 33 , and anti-CTLA4 or antibodies against programmed cell death protein 1 (PD1) can act as immune checkpoint inhibitors, increasing the T cell activity directed against tumour cells 23,26,34 .…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…A few studies also suggested that not exclusively T cells and their effective priming by DCs but also other factors contribute to abscopal anti‐tumor responses. For example, an involvement of NK cells and a negative regulation by intratumoral MDSCs have been proposed, whereas B cells appear to be dispensable . Furthermore, two groups reported on the tumor suppressor protein p53 as a mediator of RT‐stimulated abscopal effects.…”
Section: Critical Parameters Of Systemic Anti‐tumor Reactions and Absmentioning
confidence: 99%
“…For example, an involvement of NK cells and a negative regulation by intratumoral MDSCs have been proposed, 30,49,68,86,126 whereas B cells appear to be dispensable. 78,83 Furthermore, two groups reported on the tumor suppressor protein p53 as a mediator of RT-stimulated abscopal effects. Murine lung tumors and fibrosarcomas regressed upon excessive irradiation of distant healthy tissue in wildtype but not in p53 mutant mice.…”
Section: Mediators Of Systemic Abscopal Anti-tumor Effectsmentioning
confidence: 99%
“…Strictly defined, the abscopal effect is the shrinkage or disappearance of metastatic deposits after treatment of the primary tumor mass. 42,43 Evidence of this effect has been demonstrated in both mouse 44 and human models, specifically in melanoma and renal cell carcinoma. 45,46 Despite documented evidence of this effect, to the best of our knowledge there have been a minimal number of clinical cases seen in practice.…”
Section: Immunomodulatory Effects Of Rt and Rationale For Its Use Witmentioning
confidence: 99%
“…Perhaps the most studied clinical correlate of the immunogenic effects of RT, the abscopal effect has been well documented in the literature. Strictly defined, the abscopal effect is the shrinkage or disappearance of metastatic deposits after treatment of the primary tumor mass . Evidence of this effect has been demonstrated in both mouse and human models, specifically in melanoma and renal cell carcinoma .…”
Section: Optimal Timing Of Chemotherapy With Rtmentioning
confidence: 99%